أثر استخدام أرضية التعليم الإلكتروني Moodle في تحسين أداء أعضاء هيئة التدريس بجامعة محمد بوضياف بالمسيلة - حسين, قانة; عبد الله, علي (Université de M'sila, 2020)
هدفت الدراسة إلى التعرف على أثر استخدام أرضية التعليم الإلكتروني في تحسين أداء أعضاء هيئة التدريس بجامعة محمد بوضياف بالمسيلة، ولتحقيق هدف الدراسة، قمنا بتوزيع 80 استمارة استقصاء على عينة من أعضاء هيئة التدريس بجامعة محمد بوضياف بالمسيلة، وتم تحليل 73 استمارة صالحة باستخدام برنامج SPSS v.26. وقد توصلت الدراسة إلى أن استخدام أرضية التعليم الإلكتروني MOODLE لدى أعضاء هيئة التدريس بجامعة محمد بوضياف بالمسيلة جاء بمستوى مرتفع، كما أظهرت النتائج أيضا أن مستوى أداء أعضاء هيئة التدريس جاء بمستوى مرتفع، وأظهرت الدراسة أن استخدام أرضية التعليم الإلكتروني MOODLE تساهم في تحسين أداء أعضاء هيئة التدريس بجامعة محمد بوضياف بالمسيلة. The study aimed at determining the effect of using the e-learning platform (MOODLE) on the performance of the teaching staff of Mohamed Boudiaf university,M’sila . For this, 80 questionnaires were distributed to a sample that consisted of members from the teaching staff at the university. SPSS v.26 was used to analyse 73 of the appropriate questionnaires. The findings state that the e-learning platform (MOODLE) has been used by the teaching staff to a great extent. Also, the teachers exhibited a great performance in using it. Moreover, the study reveals that the use of Moodle e-learning platform helps in improving performance of the teaching staff at Mohamed Boudiaf university
Keywords: التعليم الإلكتروني، نظام MOODLE، أداء أعضاء هيئة التدريس. ; e-learning, teachers’ performance, Moodle Platform